Heart failure with mildly reduced ejection fraction: retrospective study of ejection fraction trajectory risk. (8th March 2022) - Miller, Robert J.H.; Nabipoor, Majid; Youngson, Erik; Kotrri, Gynter; Fine, Nowell M.; Howlett, Jonathan G.; Paterson, Ian D.; Ezekowitz, Justin; McAlister, Finlay A.
Abstract: Aims: Heart failure with mildly reduced ejection fraction (HFmrEF) is associated with a favourable prognosis compared with heart failure (HF) with reduced ejection fraction (EF). We assessed whether left ventricular ejection fraction (LVEF) trajectory can be used to identify groups of patients with HFmrEF who have different clinical outcomes in a large retrospective study of patients with serial imaging. Methods and results: Patients with HF and ≥2 echocardiograms performed ≥6 months apart were included if the LVEF measured 40–49% on the second study. Patients were classified as HFmrEF‐Increasing if LVEF had increased ≥10% ( n  = 450), HFmrEF‐Decreasing if LVEF had decreased ≥10% ( n  = 512), or HFmrEF‐Stable if they did not meet other criteria ( n  = 389). The primary outcome was all‐cause mortality or cardiovascular hospitalization after the second echocardiogram. Associations with time to first event were assessed with multivariable Cox analyses adjusted for age, co‐morbidities, and medications. In total, 1351 patients with HFmrEF (median age 74, 64.2% male) were included with 28.8% exhibiting stable LVEF. During median follow‐up of 15.3 months, the composite outcome occurred in 811 patients. During follow‐up, patients with HFmrEF‐Increasing were less likely to experience the primary outcome [adjusted hazard ratio (HR) 0.72, 95% confidence interval (CI) 0.60–0.88, P  < 0.001] compared with HFmrEF‐Stable. Patients with HFmrEF‐Decreasing were more likely to experience the composite outcome in unadjusted analyses (unadjusted HR 1.19, 95% CI 1.01–1.40, P  = 0.040) but not adjusted analyses (adjusted HR 1.16, 95% CI 0.98–1.37, P  = 0.092). Associations with death or HF hospitalizations were similar (HFmrEF‐Increasing: adjusted HR 0.72, 95% CI 0.59–0.88, P  = 0.005; HFmrEF‐Decreasing: adjusted HR 1.20, 95% CI 1.01–1.44, P  = 0.044). Patients with HFmrEF‐Decreasing had a similar risk of the composite outcome as patients with HF with reduced EF (adjusted HR 1.03, 95% CI 0.89–1.20, P  = 0.670). Patients with HFmrEF‐Increasing were less likely to experience the composite outcome compared with patients with HF with preserved EF (adjusted HR 0.73, 95% CI 0.62–0.87, P  < 0.001). Conclusions: Amongst patients with HFmrEF, those exhibiting positive LVEF trajectory were less likely to experience adverse outcomes after correcting for important confounders including medical therapy. Categorizing HFmrEF patients based on LVEF trajectory provides meaningful clinical information and may assist clinicians with management decisions.